La comunidad de peces en el arrecife de Puerto Viejo (Limón, Costa Rica) - Schaper, Stefan (Universidad de Costa Rica, 1996)
The fishes of the reef of Puerto Viejo were surveyed. The most dominant species was Stegastes variabilis, that defends territories aggressively. Thalassoma bifasciatum and Ophioblennius atlanticus avoid aggression by specialized behaviour. The Diversity (Shannon-Weaver) was 1.94 - 2.28, the Dominance was 47.8% - 62.9%. The reef flat is important for the juveniles (S. variabilis: 82% juveniles).